CD133+EpCAM+ Phenotype Possesses More Characteristics of Tumor Initiating Cells in Hepatocellular Carcinoma Huh7 Cells - Yi Chen; Dongke Yu; Hao Zhang; Hongwei He; Cai‐Xia Zhang; Wuli Zhao; Rong‐Guang Shao (2012)
Background: EpCAM or CD133 has been used as the tumor initiating cells (TICs) marker in hepatocellular carcinoma (HCC).We investigated whether cells expressing with both Ep-CAM and CD133 surface marker were more representative for TICs in hepatocellular carcinoma Huh7 cells.Methods: Four different phenotypes of CD133 + EpCAM + , CD133 + EpCAM -, CD133 -EpCAM + and CD133 -EpCAM -in Huh7 cells were sorted by flow cytometry.Then cell differentiation, self-renewal, drug-resistance, spheroid formation and the levels of stem cell-related genes were detected to compare the characteristics of TICs.The ability of tumorigenicity was measured in nonobese diabetic/severe combined immunodeficient (NOD/SCID) mice to verify TICs.Results: CD133 + EpCAM + cells have many characteristics of TICs in Huh7 cells compared with CD133 + EpCAM -, CD133 -EpCAM + , CD133 -EpCAM -cells, including enrichment in side population cells, higher differentiation capacity, increased colony-formation ability, preferential expression of stem cell-related genes, appearance of drug-resistant to some chemotherapeutics, more spheroid formation of culture cells and stronger tumorigenicity in NOD/SCID mice.Conclusion: CD133 + EpCAM + phenotype is precisely represented TICs in Huh7 cells.It might be useful for studying biology mechanism of TICs in hepatocellular carcinoma and screening new targets for cancer therapy.